Kajian Perancangan Karakter Maskot Universitas Pendidikan Mandalika - Fanny Printi Ardi; Pyo Apriliana Munawarah; Mi’rajus Subyan Rahmat; Lalu Aswandi Mahroni G (JTIM : Jurnal Teknologi Informasi dan Multimedia, 2021)
Mascot is a promotional media that is familiar in promotional media. Several companies to universities have mascots as icons that can represent higher education. UNDIKMA as a new joint-form campus has not used the media in the form of mascots for promotion. considering that NTB is a heterogeneous region with respect to ethnicity, religion, and race, so it requires a mascot as a brand ambassador for UNDIKMA. This is important because in the NTB region there is no tertiary institution that has a mascot. In the previous study, there was no study on mascot creation for universities. The purpose of this research is to design a mascot with a method approach that puts forward the target audience. While the method used is the Design Thinking Method developed by Tim Brown. Design thinking is a way to solve ambiguous and unfamiliar problems, rediscover problems in a human-centered way, brainstorm to generate multiple ideas, and take a hands-on approach. Very useful for prototyping and testing. Design thinking also includes continuous experimentation, such as sketching, prototyping, experimenting, and trying out different concepts and ideas. The target outcome of this research is to hopefully create a mascot design. In addition, it is also hoped that the output in the form of a mascot design guide line will also be successfully written. So that the application of the mascot can be correct and in accordance with the objectives expected by the designer.